Kreativitas Guru Pjok Dalam Metode Pembelajaran Untuk Meningkatkan Aspek Kognitif Siswa - Arya Sena Andayana Putra; Muhammad Wahyono; Ramadhany Hananto Puriana; Sitti Maifa; Jumesam Jumesam (Jurnal Porkes, 2026)
The main issue in this study is the low level of cognitive engagement among students in Physical Education, Sports, and Health (PJOK) classes at Antartika High School in Sidoarjo, both in regular classes and sports classes. Instruction is still dominated by physical activities without optimal development of conceptual understanding and critical thinking. This study aims to describe the creativity of PJOK teachers in applying question-and-answer and demonstration methods to enhance students’ cognitive aspects. The method used is a qualitative approach with a case study design. Data collection techniques include observation, in-depth interviews, and documentation. The research subjects consisted of two PE teachers and twelve students selected through purposive sampling. The results showed that teachers’ creativity in regular classes was manifested through a variety of tiered questions up to the Higher-Order Thinking Skills (HOTS) level, probing techniques, and reinforcement of reflective answers, which successfully increased student active participation from 30% to 70% and raised the average cognitive score by +16.5 points. In physical education classes, teacher creativity was manifested through step-by-step demonstrations with conceptual explanations, student involvement in peer assessment, and post-practice reflection, which increased the average cognitive score by +14.6 points. In conclusion, teacher creativity that is adaptive to class characteristics has been proven to contribute positively to the improvement of students’ cognitive aspects in physical education learning.